Odpowiedź:
3/4 - 5/8 = 6/8 - 5/8 = 1/8
7/6 - 3/4 = 14/12 - 9/12 = 5/12
3 i 1/4 + 2 i 2/5 - (4 i 1/3 - 2 i 2/3) = 3 i 1/4 + 2 i 2/5 - (3 i 4/3 - 2 i 2/3) = 3 i 1/4 + 2 i 2/5 - 1 i 2/3 = 3 i 5/20 + 2 i 8/20 - 1 i 2/3 = 5 i 13/20 - 1 i 2/3 = 5 i 39/60 - 1 i 40/60 = 4 i 99/60 - 1 i 40/60 = 3 i 59/60
10 - (2 i 1/9 - 1/2 + 1 i 5/6) = 10 - (2 i 2/18 - 1 + 1 i 15/18) 10 - (1 i 2/18 + 1 i 15/18 ) = 2 i 17/18
2/3 - 1/5 = 10/15 - 3/15 = 7/15
4/7 - 1/2 = 8/14 - 7/14 = 1/14
5 i 5/13 - 3 i 1/2 = 5 i 10/26 - 3 i 13/26 = 4 i 36/26 - 3 i 13/26= 1 i 23/26
4 i 1/4 - 2 i 2/3 = 4 i 3/12 - 2 i 8/12 = 3 i 15/12 - 2 i 8/12 = 1 i 7/12